Anti-Müllerian hormone was independently associated with central obesity but not with general obesity in women with PCOS. Issue 1 (10th January 2022) - Zeng, Xiying; Huang, Yinxiang; Zhang, Mulin; Chen, Yun; Ye, Jiawen; Han, Yan; Ma, Danyan; Zheng, Xin; Yan, Xiaohong; Liu, Changqin
Abstract : Objective: Anti-Müllerian hormone (AMH) is recognized as the most important biomarker for ovarian reserve. In this cross-sectional study, we aimed to explore the potential association of AMH with central obesity or general obesity in women with polycystic ovary syndrome (PCOS). Methods: In this cross-sectional study, 179 patients with PCOS were enrolled and underwent anthropometric measurements (BMI and waist circumference (WC)) and serum AMH level detection. Pearson's correlation and multivariable logistic regression analyses were performed to determine the associations of AMH with central obesity and general obesity. Results: Subjects with increasing BMI showed significantly lower values of AMH (median (interquartile range (IQR)) 8.95 (6.03–13.60) ng/mL in normal weight group, 6.57 (4.18–8.77) ng/mL in overweight group, and 6.03 (4.34–9.44) ng/mL in obesity group, P  = 0.001), but higher levels of systolic blood pressure, fasting insulin, total cholesterol, triglycerides, LDL-c, obesity indices (WC, hip circumferences, waist-to-hip ratio, waist-to-height ratio (WHtR), and Chinese visceral adiposity index (CVAI)). Compared with the group of PCOS women without central obesity, the group with central obesity had significantly lower value of AMH (median (IQR) 8.56 (5.29–12.96) ng/mL vs 6.22 (4.33–8.82) ng/mL; P  = 0.003). Pearson's correlation analysis showed that AMH was significantly and negatively correlated with BMI (r = −0.280; P < 0.001), WC (r = −0.263; P < 0.001), WHtR (r = −0.273; P < 0.001), and CVAI (r = −0.211; P  = 0.006). Multivariate logistic regression analysis with adjustment for potential confounding factors showed that AMH was independently and negatively associated with central obesity but was not significantly associated with general obesity. Conclusions: AMH was independently and negatively associated with central obesity. Closely monitoring the WC and AMH should be addressed in terms of assessing ovarian reserve in women with PCOS.